Aperfeiçoamento dos procedimentos de diagnóstico micológico e o perfil epidemiológico dos agentes de micoses superficiais e cutâneas na cidade de Montes Claros – MG - Gislaine Tolentino Saraiva e Alvarenga (2023)
Fungal infections are neglected diseases, presenting several challenges in relation to diagnosis, mainly due to the lack of training of laboratories and medical professionals. health. This leads to underreporting of cases and empirical treatment that can reduce the quality of life of patients and lead to the selection of drug-resistant strains commonly used in dermatological clinics. Cutaneous mycoses are fungal infections that affect a significant percentage of the world population with skin manifestations, and nail, which can be caused by filamentous fungi and yeasts. Among the fungi filamentous, dermatophytes are responsible for 25% of infections followed by yeasts of the genus Candida. Nail and skin mycoses are the infections that occur most frequently. frequency, however, the prevalence of these infections is variable and depends on parameters associated with the individual and the fungus, their mutual interactions and epidemiological and geographical. Humans of any age and both sexes can be affected by dermatomycosis, which constitutes an important public health problem. The objective of This work was to update and improve the stages of laboratory diagnosis of exams mycological, from collection to isolation and identification of the etiological agents causing cutaneous mycoses, at the Santa Clara Laboratory (LSC) in Montes Claros, MG. All the established and recognized quality parameters in the area of Clinical Mycology were reviewed and adopted. This approach made it possible to optimize laboratory procedures for microscopy and culture in specific culture media and implement methodologies for determine the susceptibility profile to the most commonly used antifungals in dermatological clinics using the broth microdilution technique and in accordance with documents M38-A and M27-A2 of the Clinical and Laboratory Standards Institute (CLSI), respectively, for fungi filamentous and yeast. Furthermore, it was possible to correlate the etiology of infections with factors related to the individual, such as the presence of comorbidities, occupation, coexistence with pets, medication use and smoking. In this way, optimization and updating mycological diagnostic methodologies allowed the correct identification of the Causer agent. Samples from 83 patients were analyzed, with a predominance of women, representing 65.06%. Of the 132 mycological tests performed, 68.18% were positive, among the 112 cultures, we reached 67.85% positivity and the work showed that onychomycosis were the main clinical manifestations, with subungual scrapings of the right and left, the places most affected, representing 59.39%. Additionally, Trichophyton rubrum was the most prevalent etiological agent, followed by Trichophyton mentagrophytes and Candida parapsilosis. The dermatophyte and yeast isolates tested in this study were susceptible to Itraconazole, Fluconazole, Terbinafine or Nystatin. Therefore, this study provides relevant information on the epidemiology of dermatomycoses that may be useful in promotion of appropriate therapeutic strategies that can prevent the emergence of resistance fungal infection, and provides the medical professional with an important diagnostic tool for assistance in the treatment of their patients, thus contributing to the improvement of quality life of patients in the city of Montes Claros.